RAW MATERIAL IMPORTATION IN BRAZIL: Challenges, Strategies, and Solutions for Sustainable Industrial Competitiveness - Barbosa Camelo, Thiago; Neto, José Benedito Tosoni Decarlis; Casagrande, Diego José (Revista Interface Tecnológica, 2025)
The importation of raw materials plays an important role in the industrial development of Brazil. By ensuring access to quality inputs, it not only strengthens productive capacity but also connects the country to the international market, enhancing competitiveness in an increasingly dynamic global scenario. This study examines the main challenges and strategies associated with import operations, applying a qualitative and descriptive methodology based on academic literature review and technical document analysis. The research relies on reputable sources and relevant materials, including Federal Revenue regulations, systems such as Siscomex and DUIMP, and the Incoterms 2020.The analysis covers essential topics in foreign trade, such as tax regimes, international logistics, exchange management, sustainability, and the role of regulatory bodies. The findings emphasize that technological modernization, with tools like real-time tracking and digitized processes, is a key element for overcoming bureaucratic obstacles. Another highlighted aspect is the importance of professional training to turn these challenges into competitive advantages. Additionally, practices aligned with the Sustainable Development Goals (SDGs) have proven to be fundamental for ensuring the strategic positioning of Brazilian companies in an increasingly demanding global market. It concludes that the importation of raw materials, when well-planned and executed, can be a strategic tool to drive industrial development and meet global demands for efficiency and environmental responsibility.